2001
DOI: 10.1557/proc-699-r4.8
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Transient Photoconductivity Studies in Porous Semiconductors

Abstract: The dynamics of the photogenerated carriers in porous silicon and TiO2 anatase was studied at 35 GHz by measuring the change in time of the conductivity s and dielectric constanter. Localization of carriers leads to a positive change ofer, while quasifree carriers to a negative change. Size reduction in Si shortens the recombination time as long as the surface traps are not significant. Magnetic field investigations show opposite variation of conductivity in poroussilicon compared with TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, time-resolved microwave studies of nanocrystalline titania (TiO 2 ) show that photoexcitation can also lead to large changes in the real component of the complex permittivity. , For example, Kytin et al have reported UV-induced changes in the real component of the microwave permittivity of 6 and 16 nm anatase particles that are comparable in magnitude to the changes in the imaginary component. Trapped electrons may also contribute to the light-induced microwave reflectance response of compound semiconductors or materials such as nanocrystalline films , and polymers …”
Section: Introductionmentioning
confidence: 99%
“…However, time-resolved microwave studies of nanocrystalline titania (TiO 2 ) show that photoexcitation can also lead to large changes in the real component of the complex permittivity. , For example, Kytin et al have reported UV-induced changes in the real component of the microwave permittivity of 6 and 16 nm anatase particles that are comparable in magnitude to the changes in the imaginary component. Trapped electrons may also contribute to the light-induced microwave reflectance response of compound semiconductors or materials such as nanocrystalline films , and polymers …”
Section: Introductionmentioning
confidence: 99%